2016
DOI: 10.1080/07391102.2015.1134346
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of Ras-related protein Rab-5A and effect of mutations in the catalytically active phosphate-binding loop

Abstract: Ras-related protein (Rab-5a) is primarily involved in the regulation of early endosome fusion during endocytosis and takes part in the budding process. During GTP hydrolysis, Rab5a was spotted in the cytoplasmic side of early endosomes in association with the GTP. Previous study suggested that the substitution of alanine with proline at position 30 of Rab5a reduces the GTPase activity around 12-fold, while, with arginine substitution stimulates the intrinsic GTP hydrolysis by 5-fold. Most of the other substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 49 publications
0
26
0
8
Order By: Relevance
“…For the latter, it was shown that binding of c-Raf Ras binding domain decreased the flexibility of the P-loop and switch regions (26). The dynamic regions of Rab5 have also been recently explored through molecular dynamics (MD) simulations (27). Although the study was primarily undertaken to explain the differences in the GTPase activities of mutants of the P-loop residue A30 of Rab5a (A30R and A30P), control MD simulations of wt-Rab5a showed higher root mean square fluctuation (RMSF) values for the switch I, switch II, and the interswitch regions (27).…”
Section: Introductionmentioning
confidence: 99%
“…For the latter, it was shown that binding of c-Raf Ras binding domain decreased the flexibility of the P-loop and switch regions (26). The dynamic regions of Rab5 have also been recently explored through molecular dynamics (MD) simulations (27). Although the study was primarily undertaken to explain the differences in the GTPase activities of mutants of the P-loop residue A30 of Rab5a (A30R and A30P), control MD simulations of wt-Rab5a showed higher root mean square fluctuation (RMSF) values for the switch I, switch II, and the interswitch regions (27).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the obtained structure was open and the lid was identical with the open crystal structure of TLL. In the absence of crystal structure, in silico methods can be helpful to study the impact of point mutations on the structure of PLA 1 . Models of PLA 1 mutants were also designed based on generated 3D structure of wild‐type using the Discovery Studio (Accelrys, San Diego, CA) software.…”
Section: Methodsmentioning
confidence: 99%
“…The plots of the 3D models were readied utilising PyMol and VMD (Visual Molecular Dynamics) 56 . The details of MD simulation method were previously described [57][58][59][60][61] .…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%